Persistent Organic Pollutants in Environment and Human Health - Mir, Farooq Ahmad (Journal of Environmental Science and Engineering Technology, 2023)
Persistent organic pollutants (POPs) are often referred to as "silent killers" due to their bio accumulative and long-term persistence. These can be found in every living thing, from plants to animals to people. These are to culprits for several environmental and human health problems. POPs are a leading cause of diabetes, obesity, endocrine disruption, cancer, cardiovascular disease, reproductive problems, and environmental damage. POP pollution and dangers are of concern to scientists, governments, and NGOs alike. This article reviews the most recent findings about the effects of POP contamination on human health and the natural environment.